Trials and Tribunals: administrative justice after PAJA and New Clicks with particular reference to the financial services industry - Horsley, Kerry (Department of Public Law, 2014)
In September 2005 the South African Constitutional Court handed down the seminal judgment of Minister of Health v New Clicks. The judgment is critical to our understanding of administrative justice in South Africa not only with regard to the applicability of administrative justice principles to the making of subordinate legislation, or administrative rule making, but also because of its wide ranging analysis of the state of administrative law in South Africa. Although the final Constitution of 1996 included a justiciable right to administrative justice, it was only with the passing of the Promotion of Administrative Justice Act [PAJA] in 2000 that this right was given effect to. The legislation was expected to both codify South Africa's common law and to introduce a system of administrative justice that was not wholly reliant on judicial review as a means of ensuring open, transparent and accountable government. The New Clicks judgment can be criticised for its lack of a truly majority judgment and the opaqueness of the justice achieved but it is to be welcomed for its certainty as regards the inter-relationship between the common law, the Constitution and PAJA. The judgment is concerned primarily with administrative rule-making but the case is analysed in this discussion with a view to extracting those principles that can be applied to administrative grievance tribunals. The practice of empowering expert tribunals to address grievances within the definition of administrative action and allowing administrators to review their own actions prior to a judicial review process is a favoured feature of administrative justice. The financial services industry is used as an example of the need for legislative consistency in the creation of such tribunals as well as a consistent standard of review of the resultant determinations, without which the advantages of tribunals as a means of achieving administrative justice are outweighed by competing jurisdictions, unnecessary costs and inefficiencies and, most significantly, the lack of justice for consumers.